2016
DOI: 10.5851/kosfa.2016.36.4.494
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenicity and Immune Toxicity of Emulsion-type Sausage Cured with Plasma-treated Water

Abstract: Cold plasma has been developed to reduce microbial contamination and to improve safety of food and medical products. In addition, the technology can be used in the manufacture of sausages without addition of nitrite. To be applied in food industry commercially, the new technology should be safe and efficient. However, toxicological test of plasma-treated food is limited. Therefore, the purpose of this study was to determine the mutagenicity and immune toxicity of the meat products cured with plasma-treated wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 24 publications
0
27
0
Order By: Relevance
“…Kim et al. () evaluated the mutagenicity and immunotoxicity of PAW‐cured meat. The results indicated no mutagenicity in the sausages based on the Ames test.…”
Section: Ntp–liquid Interactions In Foodmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim et al. () evaluated the mutagenicity and immunotoxicity of PAW‐cured meat. The results indicated no mutagenicity in the sausages based on the Ames test.…”
Section: Ntp–liquid Interactions In Foodmentioning
confidence: 99%
“…Further, the genotoxicity of reactive species requires to be studied in detailed while using this technology for food applications. Kim et al (2016) evaluated the mutagenicity and immunotoxicity of PAW-cured meat. The results indicated no mutagenicity in the sausages based on the Ames test.…”
Section: Changes In Food Qualitymentioning
confidence: 99%
“…CP could generate free radicals and ROS, modifying fatty acids and inducing lipid oxidation. [ 11 ] CP treatment is an effective method to inactivate a broad scope of microorganisms. [ 12 ] CP consists of electrons, UV, free radicals, photons, ions, and nonexcited atoms and molecules, and these particles can break the covalent bonds.…”
Section: Introductionmentioning
confidence: 99%
“… Lee et al (2016) reported no mutagenicity in chicken breast treated with APCP. Kim et al (2016) found no mutagenicity in emulsion sausage cured by plasma treated water and no immune toxicity, based on tumor necrosis factor-α levels in mice fed emulsion sausage for 32 d. In addition, no mutagenicity in pork loin ham cured by plasma treated water has been reported ( Yong et al , 2017b ). However, there are limited data that fully confirm the safety of meat and meat products treated with APCP, therefore, further testing is necessary to satisfy consumers and the authorities.…”
Section: Considerationsmentioning
confidence: 98%